Short animated film project Beauty and The Feast – color, emotion and lifeless object for 2D character animation / Nor Yusralina Mohd Yusoff - Mohd Yusoff, Nor Yusralina (Faculty of Film, Theatre and Animation, 2014)
This research project focuses on the application of color in the 2D character to create emotion in the short animation project Beauty and the Feast. It aims to evoke character's emotion by using specific colors. In Malaysian animation, this color emotion technique is rarely seen in the animation series. Therefore, the importance of this research project is to give the audience the knowledge about color emotion. Apart from that, this project is aimed to also enhance the character's emotion effectively with their situation. This research project uses qualitative which focuses on collecting data by gathering information from internet, library resources, conducting reviews on Malaysian animation and focus group interview. The results shown in this project has given a clear illustration and interpretation on the application of colors for 2D characters. Furthermore, this project does not only focus on color and emotion but it also focuses on the connection between emotion and motion of the 2D character. This research project will hopefully be able to benefit fellow animators, society and other researchers to gain knowledge about color emotion in animation